A relação entre a similaridade dos padrões voluntários de sustentabilidade e o comércio dos países exportadores de café - Secches, Ana Luiza (Universidade Federal de São Carlos, 2025)
This study investigates the effect of institutional alignment in Voluntary Sustainability Standards (VSS) adoption on the trade intensity of coffee-exporting countries. The analysis considers whether exporters tend to trade more intensively with partners that share similar sustainability standards. The methodology integrates 2022 bilateral export data with two similarity indices (Jaccard and Cosine) and the Trade Intensity Index. Results reveal a weak but statistically significant positive correlation between VSS similarity and trade intensity across all exporters. However, this association weakens or becomes negative among major producers. This suggests that smaller exporters may use VSS alignment as a strategy to overcome entry barriers and access new markets, while major producers, already operating through consolidated export channels, tend to rely more on price competitiveness, scale, and long-standing buyer relationships than on institutional convergence.
The relationship between voluntary sustainability standards similarity and trade for coffee exporting countries
Keywords: Normas Voluntárias Sustentáveis; Comércio de café; Intensidade comercial; Exportadores; Voluntary Sustainability Standards; Coffee trade; Trade intensity; Exporters; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; 12. Consumo e Produção Responsáveis